Health Insurance Utilization Pattern among Community People of Jutpani Kalika Municipality of Chitwan Nepal - Panthi, Srijana; Lohani, Suman; Manandhar, Alisha; Bansal, Prerna; Shrestha, Aayasha; Prasai, Meera (Journal of College of Medical Sciences-Nepal, 2023)
IntroductionThe Government of Nepal's Social Health Security Scheme (SHSS) is a social protection program that strives to give its inhabitants access to high-quality medical treatment without putting a financial burden on them. As a way of achieving Universal Health Coverage, this program makes an effort to overcome obstacles to utilizing health services and assure equity and access for underprivileged and poor populations. Thus, the study aimed to assess the pattern of using health Insurance Schemes by the community people of Central Nepal.MethodsA cross-sectional, descriptive, prospective study was conducted at Jutpani Kalika Nagar Palika ward No 7. A total of 274 enrolled households were taken using a non-probability, convenient sampling technique. The sample size was calculated by using the formula(n)= z 2pq/e2. Specifically designed proforma were used to assess the pattern of utilizing health insurance schemes. The collected data was entered in SPSS version 16. Descriptive analysis and Chi-square was applied.ResultsAmong 274 enrolled households, 94.9% have utilized the Social Health Security Scheme (SHSS). Among the study participants, 60.9% had utilized SHSS for laboratory services. The majority of study participants 230(94.7%) were below the poverty line and were utilizing SHSS. The education of the head of the household and the number of earning members in the family were found significantly associated with the utilization of SHSS.Conclusions The majority of people were utilizing SHSS and they were willing to continue this program and study found that people have faith in government service.